1999
DOI: 10.1046/j.1469-0705.1999.14050320.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of fetal isolated cerebral borderline ventriculomegaly: report of 31 cases and review of the literature

Abstract: In most cases, isolated borderline cerebral lateral ventriculomegaly has no consequence. However, this finding carries an increased risk of cerebral maldevelopment, delayed neurological development and, possibly, chromosomal aberrations. The optimal management of these cases remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
156
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 24 publications
12
156
0
4
Order By: Relevance
“…It is interesting that the odds increased over the years: 1 : 18 and 1 : 30 in the periods 1985-1988 and 1989-1992 respectively and 1 : 3 in the periods 1993-1996 and 1997-2000. Although there are no available data on diagnostic accuracy for borderline VM as opposed to severe VM, we speculate that overdiagnosis may in part be related to the publication of studies emphasizing the association of borderline VM with other CNS and non-CNS malformations or chromosomal abnormalities (Goldstein et al, 1990;Bromley et al, 1991;Patel et al, 1994;Bloom et al, 1997;Tomlinson et al, 1997;Vergani et al, 1998;Pilu et al, 1999;Graham et al, 2001;Greco et al, 2001;Kelly et al, 2001;Mercier et al, 2001). This might have induced overestimation of the ventricular width measurement to avoid missing associated anomalies.…”
Section: Investigation and Findingsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is interesting that the odds increased over the years: 1 : 18 and 1 : 30 in the periods 1985-1988 and 1989-1992 respectively and 1 : 3 in the periods 1993-1996 and 1997-2000. Although there are no available data on diagnostic accuracy for borderline VM as opposed to severe VM, we speculate that overdiagnosis may in part be related to the publication of studies emphasizing the association of borderline VM with other CNS and non-CNS malformations or chromosomal abnormalities (Goldstein et al, 1990;Bromley et al, 1991;Patel et al, 1994;Bloom et al, 1997;Tomlinson et al, 1997;Vergani et al, 1998;Pilu et al, 1999;Graham et al, 2001;Greco et al, 2001;Kelly et al, 2001;Mercier et al, 2001). This might have induced overestimation of the ventricular width measurement to avoid missing associated anomalies.…”
Section: Investigation and Findingsmentioning
confidence: 95%
“…Among published studies the lowest incidence (10%) of structural malformations was found by Pilu et al (1999) who considered 31 cases of borderline VM, 30 of which had an atrial width of 10-12 mm. Vergani et al report 6% of structural anomalies in cases with atrial width <12 mm and 56% in those with atrial width ≥12 mm.…”
Section: Structural Malformationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have been undertaken to compare detection rates (10-15 mm) affects about 1% of the population, while severe VM (> 15 mm) occurs in about 0.1% of the fetuses. VM is more frequent in males, however the prognosis is worse in females [18,19]. In clinical practice, some physicians use the terms 'ventriculomegaly' and 'hydrocephalus' alternatively for one condition -enlarged accumulation of the cerebrospinal fluid (CSF) in the ventricular system.…”
Section: Transvaginal Neuroimagingmentioning
confidence: 99%
“…When data from these two studies are included for analysis, together with the correct data from Ouahba's study 3 , there is actually a significant difference in abnormal neurological outcome in these two groups ( 7 (1994) 2/22 (9) 4/12 (33) Alagappan et al 8 (1994) 0/9 (0) 0/2 (0) Vergani et al 9 (1998) 0/42 (0) 0/3 (0) Lipitz et al 10 (1998) 0/14 (0) 1/12 (8) Pilu et al 11 (1999) 2/18 (11) 0/7 (0) Senat et al 12 (1999) 0/2 (0) 1/9 (11) Kinzler et al 13 (2001) 0/6 (0) 0/4 (0) Signorelli et al 14 (2004) 0/60 (0) -Gaglioti et al 4 …”
mentioning
confidence: 97%